CULTURAL HERITAGE PRESERVATION AS A COMPONENT OF CULTURAL POLICY: A GLOBAL VIEW - BILOVUS, Lesya; HOMOTIUK, Oksana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
CULTURAL HERITAGE PRESERVATION AS A COMPONENT OF CULTURAL POLICY: A GLOBAL VIEW